Potential Acceptability of a Pediatric Ventilator Management Computer Protocol*. Issue 11 (November 2017) - Sward, Katherine A.; Newth, Christopher J. L.; Khemani, Robinder G.; Page, Kent; Meert, Kathleen L.; Carcillo, Joseph A.; Shanley, Thomas P.; Moler, Frank W.; Pollack, Murray M.; Dalton, Heidi J.; Wessel, David L.; Berger, John T.; et al.
Abstract : Objectives: To examine issues regarding the granularity (size/scale) and potential acceptability of recommendations in a ventilator management protocol for children with pediatric acute respiratory distress syndrome. Design: Survey/questionnaire. Setting: The eight PICUs in the Collaborative Pediatric Critical Care Research Network. Participants: One hundred twenty-two physicians (attendings and fellows). Interventions: None. Measurements and Main Results: We used an online questionnaire to examine attitudes and assessed recommendations with 50 clinical scenarios. Overall 80% of scenario recommendations were accepted. Acceptance did not vary by provider characteristics but did vary by ventilator mode (high-frequency oscillatory ventilation 83%, pressure-regulated volume control 82%, pressure control 75%; p = 0.002) and variable adjusted (ranging from 88% for peak inspiratory pressure and 86% for FIO2 changes to 69% for positive end-expiratory pressure changes). Acceptance did not vary based on child size/age. There was a preference for smaller positive end-expiratory pressure changes but no clear granularity preference for other variables. Conclusions: Although overall acceptance rate for scenarios was good, there was little consensus regarding the size/scale of ventilator setting changes for children with pediatric acute respiratory distress syndrome. An acceptable protocol could support robust evaluation of ventilator management strategies. Further studies are needed to determine if adherence to an explicit protocol leads to better outcomes.